Prehistoric Violence as Difficult Heritage: Sandby Borg – A Place of Avoidance and Belonging - Wollentz, Gustav (Current Swedish Archaeology, 2017)
Despite an increased focus on heritage connected to violence within archaeological research projects, there has been no proper focus on the rediscovery of prehistoric massacres, from the perspective of diffi- cult heritage. Most likely, the temporal distance in- volved has led to the assumption that such research is superfluous. The ongoing excavations of an Iron Age massacre in the ring fort of Sandby Borg, on Öland, Sweden, challenges the validity of such an a priori assumption. This paper focuses on Sandby Borg through interviews conducted with the local population who grew up near the ring fort. The interviews reveal how new narratives and relations to the past have been created through the discovery. The results call for us to move away from a linear and chronological understanding of difficult heri- tage, in which time is approached as gradually ‘purifying’ difficult heritage, towards understand- ing ‘dissonance’ as inherent in each site of heritage, which can be used as a resource.